A Phenomenographic Analysis of College Students' Conceptions of and Approaches to Programming Learning: Insights From a Comparison of Computer Science and Non-Computer Science Contexts. (December 2021) - Chou, Te-Lien; Tang, Kai-Yu; Tsai, Chin-Chung
Programming learning has become an essential literacy for computer science (CS) and non-CS students in the digital age. Researchers have addressed that students' conceptions of learning influence their approaches to learning, and thus impact their learning outcomes. Therefore, we aimed to uncover students' conceptions of programming learning (CoPL) and approaches to programming learning (APL), and analyzed the differences between CS and non-CS students. Phenomenographic analysis was adopted to analyze 31 college students (20 CS-related, and 11 not) from northern Taiwan. Results revealed six categories of CoPL hierarchically: 1. memorizing concepts, logic, and syntax, 2. computing and practicing programming writing, 3. expressing programmers' ideas and relieving pressure, 4. applying and understanding, 5. increasing one's knowledge and improving one's competence, and 6. seeing in a new way. Four categories of APL were also found, namely: 1. copying from the textbook, teachers, or others, 2. rote memory, 3. multiple exploration attempts, and 4. online or offline community interactions. Furthermore, we found that most CS students held higher level CoPL (e.g., seeing in a new way) than non-CS students. However, compared with non-CS students, CS students adopted more surface approaches to learning programming, such as copying and rote memory. Implications are discussed.